Toxicity of Malaysian Medicinal Plant Extracts Against Sitophilus oryzae and Rhyzopertha dominica - Arshia Hematpoor; Sook Yee Liew; Hasmahzaiti Omar; Jamil Ahmad Shilpi; Azeana Zahari; Devi Rosmy Syamsir; Haslinda Mohd Salleh; Norsita Tohar; Rosalind Pei Theng Kim; Ahmad Kaleem Qureshi; Ayu Afiqah Nasrullah; Gomathi Chan; et al. (Penerbit UPM, 2022)
The insecticidal activities of extracts from 22 Malaysian medicinal plant extracts from 8 botanical families were tested against rice weevil: Sitophilus oryzae (L.) and lesser grain borer: Rhyzopertha dominica (F.). The extracts were obtained using hexane, methanol, and dichloromethane to extract potential biopesticides from dried leaves. The toxicity levels were examined periodically based on antifeedant activity and contact toxicity assays using treated grain assay. Hexane extracts of Alpinia conchigera, Alpinia scabra, Curcuma mangga, Curcuma purpurascens, Goniothalamus tapisoides, Piper sarmentosum , and methanol extracts of Curcuma aeruginosa, C. mangga , and Mitragyna speciosa were the most potent extracts against S. oryzae and R. dominica with lethal concentration (LC50) values of ≤ 0.42 mg/mL and ≤ 0.49 mg/mL, respectively. The contact toxicity test results showed that methanol extracts of C. aeruginosa and C. mangga , dichloromethane extracts of Cryptocarya nigra , and hexane extracts of C. mangga, and C. purpurascens resulted in 100% mortality of both pests within 28 days exposure of 5 mg/cm2 concentration.